Upaya Guru Bimbingan dan Konseling dalam Mengatasi Perilaku Maladaptif Siswa di SMPN 14 Banjarmasin - Tubagus, Satriya; Jarkawi, Jarkawi; Madihah, Husnul (Jurnal Konseling Komprehensif: Kajian Teori dan Praktik Bimbingan dan Konseling, 2020)
This study aims to describe 1). form of maladaptive behavior of students at SMPN 14 Banjarmasin Academic Year 2020/2021, 2). The factors that influence the maladaptive behavior of students at SMPN 14 Banjarmasin 2020/2021, 3) The efforts of the guidance andcounseling teachers in overcoming the maladaptive behavior of students at SMPN 14 Banjarmasin 2020/2021. The method used in this study is a qualitative method with a descriptive approach. . Sources of data in this study are: Bk teachers, homeroom teachers, andstudents of SMPN 14 Banjarmasin. Data collection techniques in this study using observation, interviews, and documentation. As for the validity of the data in this study using triangulation and participation extension. While the data analysis used in this study is the analysis of making conclusions from the whole discussion. The results of this study indicate that the maldaptive behavior of SMPN 14 Banjarmasin students in general is often done, namely truancy, playing tik tok, and making friends. The factors causing the maladaptive behavior of students at SMPN 14 Banjarmasin are, weak self-control factors, family factors, and environmental factors or peers that are not good and do not support the adjustment to the environment. The efforts that have been made by the counseling teacher in overcoming maladaptive behavior of students at SMPN 14 Banjarmasin are identifying problems, collecting student data and student backgrounds, collaborating with other teachers and parents of students in solving student problems at school, giving warnings or punishments and advice its nature educates and educates the students themselves.